A Semantic Pragmatic Study of English Jokes - Lutfi, Abbas Fadhil (Al-Adab Journal, 2019)
This work is a semantic pragmatic study of English jokes, which entails a multi-disciplinary (both linguistic and paralinguistic) analysis of selected English jokes. Jokes represent a very developed and witty mode of language that requires a good deal of ‘domestic knowledge’ as well as ‘encyclopaedic knowledge’, to use cognitive semantic terms. The study is an attempt to highlight the linguistic competence and the cognitive competence that underlie a good English joke. More often than not, there is more to jokes than mere humour and laughter. This paper tries to bring together language, cognition, and humour relying heavily on studies on the kinds of humorous phenomena which philosophers and linguists have already discussed. It is mainly concerned with unfolding the meaning construction and meaning conception aspects (both the principles and techniques) involved in English jokes, which could, at least partially, account for creativity, sense of humour, and wit within a cognitive semantic and pragmatic framework. It is hypothesized here that jokes represented by the data collected in this study are reflective of many of the mental abilities (linguistic and otherwise) unique to the human mind with respect to meaning construction and meaning conception. This is tantamount to saying that a good deal of semantic and pragmatic concepts contribute to the construction of an English joke. It is also hypothesized that jokes are, for the most part, based on breaking and/or manipulating the linguistic rules and/or the cognitive semantic-pragmatic principles in a broad sense. Authors tend to either eschew theoretical aims altogether, e.g. Alexander (1997), or present a grand theory, usually stating it in a few sentences of ordinary language, e.g. Latta (1999). In contrast, we shall proceed by examining small classes of jokes and attempting to find generalisations using technical terms that pertain to the fields that are brought together. The conclusions are summarised as preliminary empirical results, not as general predictive statements. To be more exact, we shall provide a description of particular subclasses of humorous phenomena; illustrate how various classes of jokes can be analysed relatively formally, focusing particularly on the linguistic mechanisms involved; and offer some tentative suggestions about the main information factors in simple jokes.